2000
DOI: 10.1128/mcb.20.8.2865-2873.2000
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Nuclear and Cytoskeletal Morphology and Mitochondrial Localization in Spermatozoa of Mice Lacking Nectin-2, a Component of Cell-Cell Adherens Junctions

Abstract: Nectin-2 is a cell adhesion molecule encoded by a member of the poliovirus receptor gene family. This family consists of human, monkey, rat, and murine genes that are members of the immunoglobulin gene superfamily. Nectin-2 is a component of cell-cell adherens junctions and interacts with l-afadin, an F-actin-binding protein.Disruption of both alleles of the murine nectin-2 gene resulted in morphologically aberrant spermatozoa with defects in nuclear and cytoskeletal morphology and mitochondrial localization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
148
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 39 publications
4
148
0
3
Order By: Relevance
“…Despite differences in the timing and the mechanism of defective acrosome biogenesis in Zpbp1 Ϫ/Ϫ and Gopc Ϫ/Ϫ mice, the phenotypes share an inability for proper formation and maintenance of Sertoli-spermatid junctions. Interestingly, studies characterizing the important heterotypic Nectin-2-Nectin-3 interactions at Sertoli-spermatid junctions also describe abnormally shaped Nectin-2-null and Nectin-3-null sperm with disorganized mitochondria (5,17,35), and the reported sperm morphological phenotypes are reminiscent of the descriptions of Zpbp1-null and Gopc-null sperm, underscoring a crucial role of proper Sertoli-spermatid junctions in sperm morphogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Despite differences in the timing and the mechanism of defective acrosome biogenesis in Zpbp1 Ϫ/Ϫ and Gopc Ϫ/Ϫ mice, the phenotypes share an inability for proper formation and maintenance of Sertoli-spermatid junctions. Interestingly, studies characterizing the important heterotypic Nectin-2-Nectin-3 interactions at Sertoli-spermatid junctions also describe abnormally shaped Nectin-2-null and Nectin-3-null sperm with disorganized mitochondria (5,17,35), and the reported sperm morphological phenotypes are reminiscent of the descriptions of Zpbp1-null and Gopc-null sperm, underscoring a crucial role of proper Sertoli-spermatid junctions in sperm morphogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…For example, nectin-2 and nectin-3 are expressed in Sertoli cells and spermatids, respectively, and their heterophilic transinteraction regulates the organization of the Sertoli cell-spermatid junctions (8). It has also been shown that the homozygous deletion of either nectin-2 or nectin-3 leads to male-specific infertility in mice (10,11). Another remarkable example is provided by the interaction of nectin-1 and nectin-3.…”
mentioning
confidence: 99%
“…In the seminiferous epithelium, Nectin-2, as well as Af-6, is also restricted to the Sertoli-Sertoli and Sertoli-spermatid junctions in Sertoli cells (Ozaki-Kuroda et al 2002, Mueller et al 2003. Nectin-2-deficient mice exhibit malespecific infertility and have defects in the later steps of sperm morphogenesis in the testis (Bouchard et al 2000, Ozaki-Kuroda et al 2002. Interestingly, in these mutant testes, the spermatids at steps 1 -10 of spermiogenesis were normal, but at later steps (after step 11), the defects involving irregular shapes and prominent translucent vesicles were observed in all nuclei.…”
Section: Discussionmentioning
confidence: 99%